IMPROVING SCIENCE CONTENT LEARNING OUTCOMES THROUGH APPLICATION OF PRACTICAL LEARNING METHODS FOR CLASS IV STUDENTS - Syafrilla Faigha Utami; Agung Setyawan (maktab: Jurnal Pendidikan dan Teknologi, 2022)
This study aims to determine whether the practicum method can improve student learning outcomes for grade 4 students at SDN Paseban 02. The research I did was classroom action research using a Kurt Lewin research design. The data collection techniques used in this study were interviews, observations, documentation, and tests, with data techniques going through 3 stages, namely data reduction, analysis, and drawing conclusions. The results showed that there was an increase in the average student learning outcomes. In the first cycle the average student learning outcomes are 63.12 while in the second cycle the average student learning outcomes are 83.75, then the average student learning outcomes increase by 20.63. While the percentage of student learning completeness in cycle 1 is 53.1% while in cycle 2 is 87.5%, then the percentage of student learning mastery increases by 34.4%. It can be collected, based on the data that the initial learning target of the practicum method is achieved, namely improving student learning outcomes in science subjects in class IV SDN Paseban 02.